Wednesday

July 30, 2014

July 30, 2014

Posted by **JungJung** on Friday, December 8, 2006 at 3:58pm.

(sinX)^6 +(cosX)^6= 1 - 3(sinX)^2 (cosX)^2

sinX^6= sinx^2 ^3 = (1-cosX^2)^3

= (1-2CosX^2 + cos^4) (1-cosX^2)

then multiply that out

1-2CosX^2 + cos^4 - cosX^2 + 2cos^4 -cos^6

add that on the left to the cos^6, and combine terms..

1-3CosX^2 + 3cos^4

1-3cos^2x (i-cos^2 x)

then use the sin^2 x=1-cos^2 x and you have it.

**Related Questions**

Trig........ - I need to prove that the following is true. Thanks (cosx / 1-sinx...

Pre-Calc - Trigonometric Identities Prove: (tanx + secx -1)/(tanx - secx + 1)= ...

Trigonometry. - ( tanx/1-cotx )+ (cotx/1-tanx)= (1+secxcscx) Good one! ...

Trigonometry Check - Simplify #3: [cosx-sin(90-x)sinx]/[cosx-cos(180-x)tanx] = [...

Math - Pre- Clac - Prove that each of these equations is an identity. A) (1 + ...

trigonometry - can i use factoring to simplify this trig identity? the problem ...

math - tanx+secx=2cosx (sinx/cosx)+ (1/cosx)=2cosx (sinx+1)/cosx =2cosx ...

Math - Verify the identity . (cscX-cotX)^2=1-cosX/1+cosX _______ sorry i cant ...

maths - trigonometry - I've asked about this same question before, and someone ...

Pre-calc - prove the identity: (cosx)(tanx + sinx cotx)=sinx+cos(squared)x i ...